2022
DOI: 10.3390/v14020413
|View full text |Cite
|
Sign up to set email alerts
|

High-Sulfated Glycosaminoglycans Prevent Coronavirus Replication

Abstract: Coronaviruses (CoVs) are common among humans and many animals, causing respiratory or gastrointestinal diseases. Currently, only a few antiviral drugs against CoVs are available. Especially for SARS-CoV-2, new compounds for treatment of COVID-19 are urgently needed. In this study, we characterize the antiviral effects of two high-sulfated glycosaminoglycan (GAG) derivatives against SARS-CoV-2 and bovine coronaviruses (BCoV), which are both members of the Betacoronavirus genus. The investigated compounds are ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The bovine low-sulfated chondroitin sulfate sCS3 was also reported to efficiently inhibit in vitro the viral replication of Alpha and Beta SARS-CoV-2 and the related bovine coronavirus BCoV at low IC 50 concentrations of 1.756 µM [76]. Interesting, in this study, assessing also the very efficient antiviral activity of another GAG, the modified high-sulfated hyaluronan sHA3, is the observation that the molecular weight and structure particularities of the disaccharide-repeating units determine the efficiency of the binding behaviors of sHA3 and sCS3, which have a similar degree of sulfation [76].…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…The bovine low-sulfated chondroitin sulfate sCS3 was also reported to efficiently inhibit in vitro the viral replication of Alpha and Beta SARS-CoV-2 and the related bovine coronavirus BCoV at low IC 50 concentrations of 1.756 µM [76]. Interesting, in this study, assessing also the very efficient antiviral activity of another GAG, the modified high-sulfated hyaluronan sHA3, is the observation that the molecular weight and structure particularities of the disaccharide-repeating units determine the efficiency of the binding behaviors of sHA3 and sCS3, which have a similar degree of sulfation [76].…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…A more recent example of the chemical synthesis of an sGAG mimetic was reported by Möller and co-workers, who produced fully sulfated HA and CS analogues for biological evaluation . Inhibition studies with SARS-CoV-2 infections showed greater inhibition potential of the fully sulfated HA analogue with an SI = 232.68 compared to the fully sulfated CS analogue (SI = 82.39) despite having the same degree of sulfation.…”
Section: Hs Mimetics As Viral Inhibitorsmentioning
confidence: 99%
“…Furthermore, studies have shown that hospitalized COVID-19 patients treated with low-molecular-weight heparin or ultra-low-molecular-weight heparin had improved mortality [ 135 , 136 ]. Highly sulphated HS- and CS-based compounds have also been developed for testing in COVID-19 treatment to block HS proteoglycan interaction with SARS-CoV-2 [ 137 ]. The compounds were found to inhibit SARS-CoV-2 growth in cells infected with the virus especially if the compounds were added during adsorption phase.…”
Section: The Role Of Glycosaminoglycans In Airways Diseasementioning
confidence: 99%